2002
DOI: 10.1094/cm-2002-1218-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Double‐Cropped Winter Annual Forage into a Corn‐Soybean Rotation

Abstract: Consolidation in the dairy and livestock industry in the North Central stateshas resulted in a need for producers to increase forage production per unit ofland base. Using a winter annual forage crop in a corn (Zea mays L.) andsoybean [Glycine max (L.) Merr.] cropping system could add a thirdharvestable crop in a two‐year rotation period resulting in increased forageproduction per unit of land base. The objective of this study was to: (1)evaluate the yield and quality of winter wheat (Triticum aestivum L.) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 10 publications
4
28
0
Order By: Relevance
“…Reddy (2001) also reported that RCC had no detrimental effect on soybean yield with either no-till or conventional till. With winter wheat (Triticum aestivum L.) and winter RCCs, Thelen and Leep (2002) reported soybean yield was not reduced when planted 5 to 11 d after rye control, although there were reduced yields of corn and corn silage. It appears that farmers can effectively utilize RCC in CS cropping systems when the RCC precedes soybean in the rotation.…”
Section: Soybean Plant Population and Yieldmentioning
confidence: 99%
See 4 more Smart Citations
“…Reddy (2001) also reported that RCC had no detrimental effect on soybean yield with either no-till or conventional till. With winter wheat (Triticum aestivum L.) and winter RCCs, Thelen and Leep (2002) reported soybean yield was not reduced when planted 5 to 11 d after rye control, although there were reduced yields of corn and corn silage. It appears that farmers can effectively utilize RCC in CS cropping systems when the RCC precedes soybean in the rotation.…”
Section: Soybean Plant Population and Yieldmentioning
confidence: 99%
“…However, research has found differing annual crop yield responses with RCC. Corn grain and silage yield decreases have been reported with use of RCC (Raimbault et al, 1990;Kessavalou and Walters, 1997;Thelen and Leep, 2002;Singer and Kohler, 2005;McDonald et al, 2008;Kramberger et al, 2009;Salmerón et al, 2011;Krueger et al, 2012;Reese et al, 2014). A 15% corn yield increase was observed in 2 out of 3 yr in a study conducted on sandy soils in Wisconsin with no N application to the RCC and with low RCC biomass production .…”
mentioning
confidence: 99%
See 3 more Smart Citations